Role of Sortase A in Lactobacillus gasseri Kx110A1 Adhesion to Gastric Epithelial Cells and Competitive Exclusion of Helicobacter pylori - Zuo, Fanglei; Appaswamy, Amulya; Gebremariam, Hanna G.; Jonsson, Ann-Beth (Frontiers in Microbiology, 2019)
We have previously shown that Lactobacillus gasseri Kx110A1, a human stomach isolate, can colonize mouse stomach and reduce the initial colonization of H. pylori. Here, we investigated the role of the sortase-dependent proteins (SDPs) involved in these functions by the construction of a mutant for srtA, the gene encoding the housekeeping sortase that covalently anchors SDPs to the cell surface. The mutant showed a decrease in hydrophobicity and autoaggregation under acidic conditions, indicating the effect of SDPs on cell surface properties. Correspondingly, the mutant lost the capacity to adhere to gastric epithelial cells, thus resulting in an inability to provide a physical barrier to prevent H. pylori adherence. These results indicate that sortase A is a key determinant of the cell surface properties of L. gasseri Kx110A1 and contributes to Lactobacillus-mediated exclusion of H. pylori. Understanding the molecular mechanisms by which lactobacilli antagonize H. pylori might contribute to the development of novel therapeutic strategies that take advantage of health-promoting bacteria and reduce the burden of antibiotic resistance.